The Mediating Role of Meaning in Life in the Effects of Calling on Posttraumatic Stress Symptoms and Growth: A Longitudinal Study of Navy Soldiers Deployed to the Gulf of Aden - Seol, Jeong Hoon; Park, Yonguk; Choi, Jinsoo; Sohn, Young Woo (Frontiers in Psychology, 2021)
This study examined the mediating role of meaning in life in the effect of calling on post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG) among Navy soldiers of the Republic of Korea deployed to the Gulf of Aden, Somalia. Participants responded to the questionnaire survey three times (pre-deployment, deployment, and post-deployment) at 4-month intervals. From the first, second, and third surveys, data were collected for 223, 195, and 103 respondents, respectively. Results showed that calling had a negative effect on PSTD, fully mediated by meaning in life, whereas calling had a positive effect on PTG, partially mediated by meaning in life. Our findings suggest that calling acts as a positive psychological resource for maintaining the meaning in life throughout stressful events experienced during deployment, thereby reducing post-traumatic stress symptoms and promoting post-deployment psychological growth. Finally, theoretical and practical implications and the need for follow-up studies are discussed.